2015
DOI: 10.1302/0301-620x.97b2.34891
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for the correction of hallux valgus

Abstract: This study sought to determine the medium-term patient-reported and radiographic outcomes in patients undergoing surgery for hallux valgus. A total of 118 patients (162 feet) underwent surgery for hallux valgus between January 2008 and June 2009. The Manchester-Oxford Foot Questionnaire (MOXFQ), a validated tool for the assessment of outcome after surgery for hallux valgus, was used and patient satisfaction was sought. The medical records and radiographs were reviewed retrospectively. At a mean of 5.2 years (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 45 publications
(57 reference statements)
0
2
1
Order By: Relevance
“…We were unable to identify other studies performing regression analysis for minimally invasive hallux valgus surgery, which prevented us from making comparisons. However, Chong et al performed regression analysis on a population consisting predominantly of patients treated with scarf osteotomies and found no association between radiographic evidence of severity or the degree of correction and the MOXFQ score; the latter finding contradicts ours 37 .…”
Section: Discussioncontrasting
confidence: 69%
“…We were unable to identify other studies performing regression analysis for minimally invasive hallux valgus surgery, which prevented us from making comparisons. However, Chong et al performed regression analysis on a population consisting predominantly of patients treated with scarf osteotomies and found no association between radiographic evidence of severity or the degree of correction and the MOXFQ score; the latter finding contradicts ours 37 .…”
Section: Discussioncontrasting
confidence: 69%
“…It is a complicated multiplanar pathology and is characterised by lateral deviation and valgus rotation of the hallux and medial deviation of the first metatarsal [1, 3, 4]. It has been reported that approximately 23% of adults aged between 18 and 65 years have the deformity, which increases to 35.7% of the population above 65 years of age [3]. It has a higher female predilection and can often result in a decreased quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hallux abducto valgus (HAV), the bunion deformity, is one of the most common presentations in foot and ankle practice [1, 2]. It is a complicated multiplanar pathology and is characterised by lateral deviation and valgus rotation of the hallux and medial deviation of the first metatarsal [1, 3, 4]. It has been reported that approximately 23% of adults aged between 18 and 65 years have the deformity, which increases to 35.7% of the population above 65 years of age [3].…”
Section: Introductionmentioning
confidence: 99%